Derivative-Free Characterizations of $Q_K$ Spaces II - Li, Songxiao; Wulan, Hasi (Sarajevo Journal of Mathematics, 2024)
The $Q_K$ spaces on the open unit disk are characterized by some oscillations in the Bergman metric without the use of derivatives. Our results are new even in the case of $Q_p$ spaces. 2000 Mathematics Subject Classification. 30H05, 46E15